2021
DOI: 10.1038/s41598-021-95085-5
|View full text |Cite|
|
Sign up to set email alerts
|

De novo transcriptome characterization of Iris atropurpurea (the Royal Iris) and phylogenetic analysis of MADS-box and R2R3-MYB gene families

Abstract: The Royal Irises (section Oncocyclus) are a Middle-Eastern group of irises, characterized by extremely large flowers with a huge range of flower colors and a unique pollination system. The Royal Irises are considered to be in the course of speciation and serve as a model for evolutionary processes of speciation and pollination ecology. However, no transcriptomic and genomic data are available for these plants. Transcriptome sequencing is a valuable resource for determining the genetic basis of ecological-meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Therefore, a comprehensive understanding of the MADS family and the function of key members is meaningful for the modification of crop yield and quality. In recent years, the MADS family has been identified in many horticultural plants, such as pineapple ( Zhang et al., 2020 ), apple ( Tian et al., 2015 ), pear ( Wang et al., 2017 ), tomato ( Wang et al., 2019 ), iris ( Bar-Lev et al., 2021 ), banana ( Lakhwani et al., 2022 ), chrysanthemum ( Won et al., 2021 ), pomegranate ( Zhao et al., 2020 ), rhododendron ( Huo et al., 2021 ), and litchi ( Guan et al., 2021 ). A total of 74 MADS family members were identified in the kiwifruit genome in this study, which is smaller than that in Arabidopsis (106), poplar (105) and apple (147), and comparable with that of rice (75).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a comprehensive understanding of the MADS family and the function of key members is meaningful for the modification of crop yield and quality. In recent years, the MADS family has been identified in many horticultural plants, such as pineapple ( Zhang et al., 2020 ), apple ( Tian et al., 2015 ), pear ( Wang et al., 2017 ), tomato ( Wang et al., 2019 ), iris ( Bar-Lev et al., 2021 ), banana ( Lakhwani et al., 2022 ), chrysanthemum ( Won et al., 2021 ), pomegranate ( Zhao et al., 2020 ), rhododendron ( Huo et al., 2021 ), and litchi ( Guan et al., 2021 ). A total of 74 MADS family members were identified in the kiwifruit genome in this study, which is smaller than that in Arabidopsis (106), poplar (105) and apple (147), and comparable with that of rice (75).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, transcriptomics data generated from floral and young leaf tissues were also used for the Louisiana Irises study due to the lack of genome sequencing data. Similarly, 43 MADS-box genes were identified in the de novo transcriptomics study of Iris atropurpurea , an endemic species in Israel [ 29 ]. Compared to 33 MIKC C genes identified in this study, 28 were found in the I. atropurpurea transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…We performed the phylogenetic analysis on MADS-box protein sequences from J. curcas. The MADS-box proteins regulate floral organogenesis and are essential for flower development and sex determination (De Bodt et al 2003;Pan et al 2018;Bar-Lev et al 2021). These proteins can be subdivided into two lineages, the M-type (type I) and MIKC (type II).…”
Section: Discussionmentioning
confidence: 99%